Palliative dental interventions in patients with terminal cancer: An integrative review (Research, Society and Development, 2024)
Objective: To identify the main palliative dental interventions in patients with terminal cancer, analyzing the updated scientific literature. Methodology: Integrative literature review carried out in the electronic databases BVS (LILACS and MEDLINE), Science Direct and PubMed, using the following descriptors: “Odontologia”; “Assistência Odontológica”; “Cuidados Paliativos”; “Doente Terminal”; “Neoplasias”; “Dentistry”; “Dental Care”; “Palliative Care”; “Terminal Care”; “Neoplasms” and “Cancer”. Full articles published between 2014 and 2024 were included. Results: 10 articles made up the final sample of this study. There was a higher concentration of publications in the USA and randomized clinical trials. It was possible to identify the effectiveness of palliative interventions such as the use of honey, topical morphine and bethanechol in the management of debilitating oral symptoms, such as mucositis and xerostomia. The results show that such interventions not only provide immediate symptomatic relief, but also contribute to maintaining the quality of life of terminally ill patients. Conclusion: This review highlighted the importance of integrating dental care into multidisciplinary teams, pointing to the need for greater training and awareness among healthcare professionals about the critical role of palliative dentistry. Therefore, future research should explore the application and effectiveness of these interventions in different clinical contexts, aiming to improve palliative care practices in dentistry.